An assessment of climate action by high-carbon global corporations. Issue 12 (December 2018) - Dietz, Simon; Fruitiere, Charles; Garcia-Manas, Carlota; Irwin, William; Rauis, Bruno; Sullivan, Rory
Abstract Corporations are an important source of GHG emissions1–3 and important actors in mitigating climate change4 . This paper presents and analyses a database of corporate climate action that provides an up-to-date assessment of companies' carbon management practices, as well as systematically benchmarking companies' emissions pathways against international targets. Our analysis covers 138 companies in 7 high-emitting sectors, accounting for 21% of emissions from all listed companies globally5 . While most companies have implemented basic carbon management practices, we find that less than half of them have implemented more strategic practices. Further analysis indicates companies separate into those that hardly undertake any carbon management practices and those that undertake most. Perhaps surprisingly, most corporate emissions targets in our sample are aligned with the Paris Agreement goals, although most companies are yet to set quantified targets. Companies that have implemented more carbon management practices today are more likely to have set 2 °C-aligned targets. Carbon management and emissions performance are associated most strongly with where companies are headquartered and their size. Corporations are an important source of GHG emissions and an important climate-mitigation actor. An assessment of corporate climate action and systematic benchmarking against international targets is conducted for 138 companies in high-emitting sectors.